Synthesis and characterization of some derivatives five hetrocyclic ring - Jaafar, Noor Saad; Ghanim, Hasan Thamir (Al-Qadisiyah Journal of Pure Science, 2017)
In theis paper,anew series of 3-[(2-hydroxy naphthalene-1-yl)diazenyl)benzoic acid [1],ethyl 3-[(2-hydroxy naphthalene -1-yl)diazenyl]benzoate[2], 3-[(2-hydroxy naph thalene -1-yl)diazeyl] benzohyrrazide[3], [3,5-dimethyl-1H-pyrazole-1-yl] [3-[(2-hydroxy naphthalene-1yl)diazenyl)phenyl]methanone[4],[3-[(3-hydroxy naphthalene-2-yl)-diazenyl)phenyl](5-mercapto-1,3,4-thiadiazole-2-yl) methanone[5], 2-[3- [(3-hydroxy naphthalene-2-yl)diazenyl]benzoyl]-N-phenyl hydrazine carbothio amide [6],1-[(3-(5-mercapto-4-phenyl-4h-1,2,4-teiazole-3- yl)phenyl)diazenyl] naphthalene-2-ol[7], 1-((3-(5-(phenylamino)-1,3,4-thiadiazol-2- yl)phenyl)diazenyl) naphthalen-2-ol[8], (3-((2-butoxynaphthalen-1- yl)diazenyl)phenyl)(5-(butylthio)-1,3,4-thiadiazol-2-yl)methanone[9]. have been synthesized. These compounds were characterized by FT-IR ,spectrum,H1-NMR spectrum, elemental analysis and the melting point were checked, the purity of the prepared compounds were determind by TLC technique.